Pinocchio - Collodi, Carlo; Daynes, Katie; Evangelista, Mauro; Kelly, Alison (London Usborne, 2007)
'Only good sons have the chance of becoming real boys', warns the wise cricket. But, try as he might, Pinocchio the puppet just can't stay out of trouble. Treasure hunts, false friends and funfairs lead him far from his poor, lonely father. Is Pinocchio doomed to be wooden forever?
English Stories
2 13
Keywords: English Stories